Unruptured intracranial aneurysms conservatively followed with serial CT angiography: could morphology and growth predict rupture?. (25th November 2013) - Mehan, William A; Romero, Javier M; Hirsch, Joshua A; Sabbag, David J; Gonzalez, Ramon G; Heit, Jeremy J; Schaefer, Pamela W
Abstract : Background and purpose: Despite several landmark studies, the natural history of unruptured intracranial aneurysms (UIA) remains uncertain. Our aim was to identify or confirm factors predictive of rupture of UIA being observed conservatively with serial CT angiography (CTA) in a North American patient population. Methods: We performed a retrospective review of patients with UIA being followed with serial CTA studies from 1999 to 2010. The following features for each aneurysm were cataloged from the official radiologic reports and CTA images: maximum diameter, growth between follow-up studies, location, multiplicity, wall calcification, intraluminal thrombus and morphology. Univariate logistic regression analysis of the potential independent risk factors for aneurysm rupture was performed. Statistically significant risk factors from the univariate analysis were then entered into a multivariate logistic regression analysis. Results: 152 patients with a total of 180 UIA had at least two CTA studies. Six aneurysms in six different patients ruptured during the CTA follow-up period for an overall rupture rate of 3.3% and an annual rupture rate of 0.97%. All ruptured aneurysms were ≥9 mm. In the univariate analysis, the statistically significant predictors of aneurysm rupture were aneurysm size (p=0.003), aneurysm growth (p<0.0001) and aneurysm multilobulation (p=0.001). The risk factors that remained significant following the multivariate analysis were growth (OR 55.9; 95% CI 4.47 to 700.08; p=0.002) and multilobulation (OR 17.4; 95% CI 1.52 to 198.4; p=0.022). Conclusions: Aneurysm morphology and interval growth are characteristics predictive of a higher risk of subsequent rupture during conservative CTA follow-up.